Impact assessment of Maghirupay Development Program in selected communities in San Jose, Antique. - Gonzales, Eleonor R.; Luison, Jirah Kaye. (2011.)
Seventy (70) beneficiaries pf the Maghirupay Development Program of the Palanan-Awon Pangkauswagan san Antique supported by the World Vision Development Foundation in durog, Malaiba and San Angel in San Jose, Antique were selected through random sampling for this study. They are the Registered Families whose children are supported by the program. their age ranged from 13 to 65 years old. The Likert Scale was utilized for the survey along with the questionnaire, interview schedule and focus group discussion guide. Results show that the Maghirupay Development Program is no longer effective and did not create a big impact on any of its components, the Spiritual Nuture, health and Sanitation, Education amd Economic and Livelihood Development. Respondents and informants shared their insights on the organization and recommendation for its improvement
Research Project (Undergraduate, Bachelor of Arts in Community Development-Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Maghirupay Development progam -- San Jose, Antique